Pengaruh Kualitas Pelayanan dan Fasilitas Kantor terhadap Kepuasan Nasabah di Bank Bjb Kantor Cabang Pembantu Cicalengka - Asep Abdul Halim; Ade Iskandar Nasution; Anis Siti Humairoh (Jurnal Dimamu, 2021)
Based on the results of interview with the Customer Service at bank BJB Cicalengka Branch Office Assistant, there's fluctuant customer amount during 5 last years period 2016 – 2020. That's suspected of there's some complains from customers about service quality and office facilities like some important machine does'nt work so that's impact to customer satisfaction. This research aims to determine how the influence of service quality on customer satisfaction, the influence of office facilities on customer satisfaction and to determine how the influence of service quality and office facilities on customer satisfaction. The object of research in this report is the customer in bank BJB KCP Cicalengka with the type of research is quantitative associative, in order use primary data wich is taken directly from the place of research. The research sample is taken from 1440 customers at 2020 period in bank BJB Cicalengka Branch Office Assistant. The result of this research show that there is no significance influence between service quality on customer satisfaction, there is significance influence between office facilities on customer satisfaction, And the simultaneosly test show that there is significance influence between service quality and office facilities on customer satisfaction.